PENGARUH BRAND IMAGE, LABEL HALAL DAN PRODUCT QUALITY TERHADAP CONSUMER SATISFACTION PRODUK MERHAN CV FADA FOOD MOJOKERTO - Shandy Darma Pramulia; Eny Setyariningsih; Kasnowo (Jurnal Cakrawala Ilmiah, 2022)
This study aims to examine and analyze the effect of Brand Image, Halal Label and Product Quality on Consumer Satisfaction of Merhan products in the food industry of CV Fada Food Mojokerto. This study uses a quantitative descriptive approach. The technique collected in the form of primary data through a questionnaire distributed to respondents called a questionnaire. The data collection technique uses the purposive sampling technique, which is a sampling technique with certain considerations, namely using certain criteria such as CV Fada Food consumers who live in the Mojokerto area, CV Fada Food consumers aged 17 years and over, CV Fada Food consumers who have made a minimum purchase 1 time, with a total of 100 respondents at CV Fada Food. The results showed that the results of the Brand Image variable had a partially significant positive effect on Consumer Satisfaction, the Halal Label variable had a partially significant positive effect on Consumer Satisfaction and the Product Quality variable had a partially significant positive effect on Consumer Satisfaction, this was proven through the t test with the SPSS program. 25. As well as the variables Brand Image, Halal Label and Product Quality simultaneously have a significant positive effect on Consumer Satisfaction, this is proven through the F Test with the SPSS 25 program. As a form of implication of this research, it is hoped that the influential variables can be evaluated and maintained to be even better by CV Fada Food..